Students’ Perception Of E-Learning In English Language Education, Universitas Internasional Batam - Theodesia Lady Pratiwi; Kurniati Kurniati (Institut Agama Islam Negeri Palopo, 2022)
English has been taught in face-to-face class. However, since Covid-19 exploded into a global pandemic and Indonesia confirmed the first case on 2 March 2, 2020, the local government implement a policy to dismiss schools for avoiding a wider spread of the virus in schools. Covid-19 shifted the way students learn from the traditional face-to-face class to long-distance classes or what is called online class. Still, the way online class is something very new for both students and teachers. As a result, the objective of this study is to find the students’ perception of e-learning in English Language Education in Universitas Internasional Batam, this study is conducted. The quantitative method was used by conducting a survey toward 79 students in English Language Education Department. The instrument of data collection were close-ended questions and interview. By concerning the advantage, confidence, effectiveness, and efficiency of utilizing e-learning, the result shows that the average score of the categories is 2.915 which is categorized as positive perception of e-learning.